Rebolusyong 1896 [videorecording] totoo ban - Abaya, Marilou Diaz; David, Randy; Millado, Ces (Public Forum, 1996)
A Public Forum episode on the fact of Revolution 1896 discussed by Randy David with professors/historians, Bro. Ambeth Ocampo, Dr. Vivencio Jose and Dr. Milagros Guerrero.